PENGARUH SOSIOLOGI KRITIS, KREATIFITAS, DAN MENTALITASTERHADAP PENDIDIKAN AKUNTANSI - Hamzah, Ardi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
This research aim to test the effect of critical sosiology, creativity, and mentality on accounting education, simultaneously and partially. The respondents of the research are accounting students at Trunojoyo University. Purposive sampling technique is chosen with criteria respondents have done critical sosiology, creativity, and mentality. Data has gathered by questionnaires and documentation. Data analysis to test hypothesis is done with multiple linear regression analysis. The result of simultaneously regression indicate that critical sosiology, creativity, and mentality has significantly effect on accounting education. For examine of partially regression indicate only creativity that has significantly effect on accounting education. This shows that creativity still priority in accounting education than critical sosiology and mentality. Â